2006
DOI: 10.1124/dmd.105.009050
|View full text |Cite
|
Sign up to set email alerts
|

Selective Effects of Nitric Oxide on the Disposition of Chlorzoxazone and Dextromethorphan in Isolated Perfused Rat Livers

Abstract: ABSTRACT:The rapid and direct effects of nitric oxide (NO) donors sodium nitroprusside (SNP) and isosorbide dinitrate (ISDN) on the hepatic and biliary disposition of chlorzoxazone (CZX), a marker of CYP2E1, and dextromethorphan (DEM), a marker of CYP2D1, were studied in a single-pass isolated perfused rat liver model. Livers (n ‫؍‬ 30) were perfused with constant concentrations of NO donors (0-120 min) in addition to infusion of CZX or DEM (60-120 min), and periodical outlet and bile samples were collected. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…These data suggest that although ISDN-500 does not affect the Mrp2-mediated biliary transport of RH-Glu (no change in its CL bile ), it may affect the formation of the metabolite (reduced recovery). Indeed, our own previous work [8] showed that SNP and ISDN at a concentration of 400 M significantly inhibited the glucuronidation of dextrorphan and 3-hydroxymorphinan, two metabolites of dextromethorphan, in an IPRL similar to that used here. Collectively, our data using RH-123 and its glucuronidated metabolite suggest that whereas SNP-400 reduces the biliary transport of both RH-123 (P-gp) and RH-Glu (Mrp2), neither process is affected by ISDN.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These data suggest that although ISDN-500 does not affect the Mrp2-mediated biliary transport of RH-Glu (no change in its CL bile ), it may affect the formation of the metabolite (reduced recovery). Indeed, our own previous work [8] showed that SNP and ISDN at a concentration of 400 M significantly inhibited the glucuronidation of dextrorphan and 3-hydroxymorphinan, two metabolites of dextromethorphan, in an IPRL similar to that used here. Collectively, our data using RH-123 and its glucuronidated metabolite suggest that whereas SNP-400 reduces the biliary transport of both RH-123 (P-gp) and RH-Glu (Mrp2), neither process is affected by ISDN.…”
Section: Discussionmentioning
confidence: 78%
“…Elevated levels of this important bioregulator are observed in a number of hepatic disorders, such as inflammation, cirrhosis, and chronic exposure to cholesterol and alcohol [2][3][4]. Earlier works from our laboratory [5][6][7][8] and by others [2,[9][10][11][12] have shown inhibition of the expression and activities of many isoenzymes of the hepatic drug metabolizing enzymes cytochrome P450 (P450) in the presence of increased concentrations of NO. Thus, diseases that cause an upregulation of NO production, such as septic shock, have been shown to alter drug metabolism [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The procedures for the isolation and perfusion of the livers were similar to those reported before. 19,22,23 In brief, after opening the abdominal wall, bile duct, portal vein (inlet), and suprahepatic vena cava (outlet) were cannulated. The livers were then transferred to a water jacketed (37 • C), all glass perfusion system (Radnoti Glass Technology Inc., Monrovia, California) and perfused in a singlepass manner at a constant flow rate of 30 mL/min [∼3-4 mL/(min g) liver].…”
Section: Iprl Studiesmentioning
confidence: 99%
“…A different experimental approach, utilized from the 19th century onwards, consists of the use of ex vivo perfused models for the study of liver physiology [5,6], metabolism [7], and drug toxicity [7][8][9][10][11]. Ex vivo perfusion maintains normal physiological parameters, histology, and hepatocyte function for relatively prolonged periods, allowing analysis of the organ's responses to biochemical and hormonal variations [12][13][14].…”
Section: Introductionmentioning
confidence: 99%